A Simultaneous Analysis of Turnout and Voting under Proportional Representation: Theory and Experiments - Aaron Kamm; Arthur Schram (Tinbergen Institute, 2013)
In a system of proportional representation, we study the interaction between a voters turnout decision and her party choice, and how these relate to party polarization. Quantal response equilibria predict such interaction effects. In particular they predict (i) a Polarization Effect: reduced strategic party choice when voting is voluntary makes voters more likely to vote for extreme parties (conditional on voting at all); (ii) an Extremist Effect: voters supporting extreme parties are most likely to vote; (iii) a Turnout Effect: party polarization increases voter turnout. We provide data from a laboratory experiment that support these theoretical predictions. In addition, we provide supporting empirical evidence from real world elections. Hence, the interaction between turnout and strategic voting that has been neglected in most of the previous literature is shown to be important.
Keywords: C92; D72; 330; Voting behavior; Proportional representation; Political participation; Strategic voting; Experimental Economics